Market Reaction to Green Sukuk and Conventional Sukuk: An Event Study Approach - Mastiah Mastiah; Aura Nabilat En Najla; Wahyu Novriansyah; Rahma Lia (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Amid the growing emphasis on sustainable finance, green sukuk has emerged as an innovative financial instrument that integrates Islamic principles with environmental objectives. This study aims to examine the reaction of the Indonesian capital market to the Government of Indonesia’s announcements of green sukuk and conventional sukuk issuance. Using an event study approach, this research adopts a quantitative explanatory design to evaluate the informational content of these announcements and their impact on investor behavior. The Indonesia Composite Index (IHSG) is employed as a proxy for overall market performance. The observation period covers eleven trading days, consisting of five days before the announcement, the announcement day, and five days after. Expected returns are estimated using the mean-adjusted model, which are then used to calculate Abnormal Returns (AR) and Cumulative Abnormal Returns (CAR) to capture market reactions. Statistical tests, including the One-Sample t-test and Independent-Sample t-test, are conducted to assess the significance of market responses and to compare reactions between green and conventional sukuk. The findings indicate that sukuk issuance announcements do not generate statistically significant market reactions, as CAR values are not significantly different from zero. Furthermore, no significant difference is found between green sukuk and conventional sukuk, suggesting that investors have not yet fully incorporated sustainability considerations into their investment decisions. This study contributes to the literature on Islamic sustainable finance by providing empirical evidence from an emerging market context.